Du soupçon à la mobilisation ethnique: pentecôtisme gitan et ethnogénèse en Andalousie - Delgado, Manuela Cantón; Soldevila, Elena; Beaucage, Pierre (Anthropologica, 2022)
Pentecostal Churches represent one of the most original and ignored organizational experiments among Spanish Gypsies. They constitute a space of diversity within diversity. These churches embody, in various ways, the germ of a process of ethnogenesis and they illustrate, once more, that there are several very different ways to be Gypsy. The double prejudice to which Pentecostal Gypsies were initially subjected, as members of both an ethnic and a religious minority, weighed heavily in the constitution of their new identity as believers and yielded a space, for a few years, for the strategic mobilization of ethnicity and the reinvention of a more positive self-image that yielded public recognition and resources.